Solar photovoltaic energy optimization methods, challenges and issues: A comprehensive review - Al-Shahri O.A.; Ismail F.B.; Hannan M.A.; Lipu M.S.H.; Al-Shetwi A.Q.; Begum R.A.; Al-Muhsen N.F.O.; Soujeri E. (Elsevier Ltd, 2023)
Conversion efficiency; Cost reduction; Global warming; Investments; Solar power generation; Global warming problems; Intelligent optimization method; Operation and maintenance; Operational parameters; Power conversion efficiencies; Renewable energy systems; Solar energy applications; Solar photovoltaic energies; Solar energy